Mitos e possibilidades do ensino de música no contexto escolar : uma análise crítica à luz da teoria histórico-cultural - Souza, Carlos Eduardo de (Universidade Federal de São Carlos, 2016)
The present work discusses the theme of music teaching in the school context, Under the light of the Cultural-Historical Theory elaborated by Vigotsky. The objective of the research was to understand the scope of musical education in human development, taking into account the assumptions of the Historical-Cultural Theory. Music is discussed as the exclusive product of human activity. The development of musical creations accompany the transformations that arise in society and are closely related to them. In order for us to understand music as a cultural manifestation, we must consider the material and historical conditions in which it was constructed, as well as, the meaning it assumes in the different places in which it is produced. The presence of music in the school context is presented and discussed from the literature of Music Education and is justified in this space by adding to the student the specific knowledge of this area. In this way, when learning music the student is led to understand the relation between the sounds and the cultural meanings set in them. In the methodology are presented the theoretical assumptions of Marx's historical and dialectical materialism, as well as, the methodological procedures that characterize the study as theoretical. The discussion of the sources found present the social nature of human talent and the possibilities of every human being to develop them, seeking to overcome conceptions that naturalize this capacity. Also discussed are the possibilities of developing the processes of imagination and creation through musical activities, indicating the importance of mediation of teaching activity in the formation of these psychic functions in students. And finally, the possibilities of psychic transformation that music learning can generate in human beings are presented, taking into account, especially, the specific abilities that can be developed through this practice, such as auditory and aesthetic perception.
Keywords: Teoria histórico-cultural; Funções psíquicas superiores; Educação musical; Atividade docente; Historical-cultural Theory; Superior psychic functions; Musical education; Teaching activity; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM